Women and children first : feminism, rhetoric, and public policy - Meagher, Sharon M.; DiQuinzio, Patrice, 1955- (SUNY series in gender theory., 2005)
"This diverse collection explores the rhetoric of a wide range of public policies that propose "to put women and children first," including homeland security, school violence, gun control, medical intervention of intersex infants, and policies that aim to distinguish "good" from "bad" mothers. Using various feminist philosophical analyses, the contributors uncover a logic of paternalistic treatment of women and children that purports to protect them but almost always also disempowers them and sometimes harms them. This logic is widespread in contemporary popular policy discourse and affects the way that people understand and respond to social and political issues. Contributors rethink basic philosophical assumptions concerning subjectivity, difference, and dualistic logic in order to read the rhetoric of contemporary public policy discourse and develop new ways of talking and acting in the policy domain."--Jacket